Effect in the reproduction of north-center Peruvian anchovy Engraulis ringens (Jenyns, 1842) stock from Peru during La Niña Event 2017-2018 categorized by reproductive index anomalies - Cuba, Antonio (2023)
The Peruvian anchovy is a pelagic fish which is distributed in Humboldt Current System, divided in 3 stocks, being the north-center stock of Peru the most important for its high biomass values. The reproductive behavior of Peruvian anchovy was widely studied and could be affected by oceanographic changes. The aim of this work was to evaluate the reproductive strategy and the effect of La Niña 2017-2018 over the reproduction of Peruvian anchovy trough the study of the reproductive index anomalies. The time series of the reproductive index, gonadosomatic index and spawning fraction during 2017 and 2018, were given by IMARPE. The estimation and categorization of the reproductive index anomalies were done as of the methodology of Cuba et al. The results showed that in the first 3 months of the event the reproductive activity had positive anomalies with moderate effect, then positive anomalies without effect were registered. The spawning activity had a positive moderate anomaly during February, month when the anchovy presents their second important reproductive moment.